Understanding the Structural Phase Transitions in Na3V2(PO4)3 Symmetrical Sodium‐Ion Batteries Using Synchrotron‐Based X‐Ray Techniques. Issue 2 (16th December 2021) - Thangavel, Ranjith; Han, Daseul; Moorthy, Brindha; Ganesan, Bala Krishnan; Moorthy, Megala; Park, Yongll; Nam, Kyung‐Wan; Lee, Yun‐Sung
Abstract: Sodium‐ion batteries (SIBs) hold great potential for use in large‐scale grid storage applications owing to their low energy cost compared to lithium analogs. The symmetrical SIBs employing Na3 V2 (PO4 )3 (NVP) as both the cathode and anode are considered very promising due to negligible volume changes and longer cycle life. However, the structural changes associated with the electrochemical reactions of symmetrical SIBs employing NVP have not been widely studied. Previous studies on symmetrical SIBs employing NVP are believed to undergo one mole of Na + storage during the electrochemical reaction. However, in this study, it is shown that there are significant differences during the electrochemical reaction of the symmetrical NVP system. The symmetrical sodium‐ion cell undergoes ≈ 2 moles of Na + reaction (intercalation and deintercalation) instead of 1 mole of Na + . A simultaneous formation of Na5 V2 (PO4 )3 phase in the anode and NaV2 (PO4 )3 phase in the cathode is revealed by synchrotron‐based X‐ray diffraction and X‐ray absorption spectroscopy. A symmetrical NVP cell can deliver a stable capacity of ≈ 99 mAh g ‐1, (based on the mass of the cathode) by simultaneously utilizing V 3+ /V 2+ redox in anode and V 3+ /V 4+ redox in cathode. The current study provides new insights for the development of high‐energy symmetrical NIBs for future use. Abstract : The structural studies utilizing synchrotron‐based X‐ray diffraction in symmetrical sodium‐ion battery employing Na3 V2 (PO4 )3 as both the cathode and anode shows ≈2 moles of Na + reaction (intercalation and deintercalation) instead of 1 mole of Na + . A simultaneous formation of Na5 V2 (PO4 )3 phase in the anode and NaV2 (PO4 )3 phase in the cathode is verified.